Studi Historis Perguruan Taman Siswa Kota Cirebon Tahun 1923-1945 - SITI KHODIJAH (Jurnal Tamaddun, 2023)
Taman Siswa College is one of the oldest educational institutions in Indonesia which was born from the Dutch colonial era in 1922 in Yogyakarta by Ki Hadjar Dewantara. The development of Taman Siswa was so fast that it established its branch in Cirebon City in 1923. Over time, the historical existence of Taman Siswa was not widely known by the people of Cirebon in particular and those outside the City of Cirebon in general. Therefore, researchers examined the data obtained from the field, both in the form of literature and oral sources relating to the Taman Siswa College in Cirebon City in 1923-1945 with the hope that the people in Cirebon City in particular and people outside Cirebon City generally know the history of Taman Siswa. Cirebon branch. The data that the researchers studied used historical methods, namely heuristics, verification, interpretation, and historiography. From the data sources studied, it can be concluded that the Taman Siswa College of Cirebon was founded by Cirebon scholars such as Dr. Utara and friends. They tried to revive the education of children in Cirebon with the thoughts of Ki Hadjar Dewantara, namely moral education for the nation's character through the principles contained in the Taman Siswa motto: ing ngarsa sung tuladha, ing madya mangun karsa, tut wuri handayani.